Meta-Analysis Effects of Antenatal Care Visit and Knowledge on the Adherence of Iron Tablet and Folic Acid Consumption - Adhila, Siti Fatimah Aminah Nikita Putri; Budhiastuti, Uki Retno; Adriani, Rita Benya (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Adherence to iron tablet and folic acid (IFA) supplementation is the main strategy for the prevention and control of iron deficiency and neural tube defects in pregnant women and the unborn child. This study aims to estimate the relationships of antenatal care (ANC) visits and maternal knowledge on IFA supplementation adherence in pregnant women. Subjects and Method: This study is a systematic review and meta-analysis using the PRISMA flow chart and the PICO model. Population: pregnant women. Intervention: conduct antenatal care visits and have knowledge of IFA Supplementation. Comparison: did not make antenatal care visits and had no knowledge of IFA Supplementation. Outcome: IFA consumption compliance. The databases used are PubMed, Google Scholar, and SpringerLink with keywords (“Antenatal Care” OR “IFA Supplementation” OR “Compliance”) AND “cross sectional”. There were 11 cross-sectional studies published in 2011-2023 that met the inclusion criteria. Analysis was performed with RevMan 5.3. Results: A meta-analysis of 11 cross-sectional studies from Ethiopia and Uganda was performed, with sample size= 4,367. This study showed that pregnant women who had regular ANC visits (aOR=2.22; 95% CI= 1.52 to 3.24; p < 0.001) and had good knowledge (aOR=2.48; 95% CI= 2.02 to 3.03; p<0.001) were more likely to adhere to IFA supplementation. The funnel plot indicates publication bias (overestimate). Conclusion: Pregnant women with regular ANC visits and good knowledge have the possibility to adhere with IFA supplementation. Keywords: antenatal care, knowledge, adherence. Correspondence: Siti Fatimah Aminah Nikita Putri Adhila. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java 57126, Indonesia. Email: putriadhila00@gmail.com Mobile: +6282186635526.